EFISIENSI PENGGUNAAN MODAL, JAM KERJA, BAHAN BAKU TERHADAP PRODUKSI PATUNG BATU PARAS DI KECAMATAN MENGWI - Putra, I Putu Gede Wirama; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
The handicraft industry very important role in the province Bali, generally in Badung regency, especially in providing employment opportunities for the community. The purpose of this study is to analyze 1) the effect of partial factors of capital, working hours and raw materials on the value of production, 2) The simultaneous influence of capital factors, working hours, and raw materials on production value, 3) Knowing the level of efficiency of capital use, working hours, raw materials to the production value of the sandstone work sculpture in Mengwi District. This research was conducted in Badung Regency with respondents of sandstone sculpture craftsmen covering Mengwi District. The sample in this study amounted to 44 respondents. The data collection method used is multiple linear regression analysis. Based on the results of the study, it was concluded that capital, working hours and raw materials had a direct and significant effect on the production of sandstone sculpture. Variable capital, working hours and raw materials have a direct and significant effect on the production of sandstone sculpture in Mengwi District. The production variable is a dependent variable that directly influences the capital and working hour variables on raw materials. Keywords: Capital, Working Hours, Raw Materials, Production